Pendidikan Islam Dalam Sekolah Rakyat (SR): Institusi Pendidikan Yang Dikelola Pemerintah Pada Masa Kolonial - Anam, Khoirul; Maimun, Maimun; Holik, Abdul (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2025)
This study examines the role and contribution of Sekolah Rakyat (SR) as a government-managed educational institution during the colonial period in Indonesia, with a particular focus on Islamic education. Sekolah Rakyat was established in response to the need for inclusive and accessible education, especially for marginalized groups. Through historical analysis, this article reveals how Islamic education was integrated into the SR curriculum, aiming not only to provide religious knowledge but also to foster students' character and morality. Additionally, this research explores the challenges and dynamics faced by SR within the context of colonial policies and its impact on the development of Islamic education in society. Thus, this article provides an in-depth insight into the significance of Islamic education within formal education during the colonial era and its implications for education in Indonesia today